Comparison of real time PCR with phenotypic methods in bronchoalveolar lavage in diagnosis of sputum smear negative pulmonary tuberculosis patients - Agarwal, Abhishek; Pandey, Saurav; Verma, S. K.; Verma, Anand; Raza, Tasleem; Kant, Surya (International Journal of Research in Medical Sciences, 2018)
Background: Early diagnosis of pulmonary tuberculosis is of utmost importance for proper control of the disease in the patient. Diagnosis of pulmonary tuberculosis is usually by acid fast bacilli (AFB) smear examination and culture Mycobacterium tuberculosis (MTB). In this study, we have employed polymerase chain reaction (PCR) for MTB in bronchoalveolar lavage (BAL) along with AFB smear and culture MTB for early diagnosis of pulmonary tuberculosis. Methods: A prospective observational study was conducted in the Department of Pulmonary Medicine, Era’s Lucknow medical college and Hospital, Lucknow over a period of two years. A total of 123 previously treated cases of pulmonary tuberculosis were enrolled for the study whose two sputum smear samples were negative for AFB. These patients underwent fibreoptic bronchoscopy and BAL was obtained which was sent for AFB smear, culture MTB and PCR for MTB. Results: The examination of BAL revealed the highest sensitivity for culture MTB at 87.4% followed by PCR for MTB at 73.8% and then AFB smear at 61.2%. PCR for MTB helped in diagnosing an additional 12% patients of pulmonary tuberculosis which were negative on AFB smear and an additional 6.8% patients which were negative on culture MTB. Conclusions: PCR for MTB is useful in making an early diagnosis of pulmonary tuberculosis especially in paucibacillary cases negative on AFB smear and also in some culture MTB negative patients.